Psoriasis as an autoimmune disease - Owczarczyk-Saczonek, Agnieszka; Placek, Waldemar (Dermatology Review/Przegląd Dermatologiczny, 2014)
Nowadays it is known that psoriasis belongs to the group of autoimmune diseases and may coexist with other diseases in this group. Most often patients have psoriatic arthritis, rheumatoid arthritis, inflammatory bowel disease, autoimmune thyroid diseases and multiple sclerosis. The coexistence of these disorders can be a diagnostic and therapeutic problem (there is controversy over the use of corticosteroids). The common pathogenesis is still not explained. We know that the loss of immunotolerance leads to formation of autoreactive Th1 and Th17 lymphocytes which recognize self-antigens and lead to their destruction in the target organ. Some features of immune mechanisms, observed in psoriasis, suggest its autoimmune background. In psoriasis the main role is played by the activation of the axis IL-12/Th1/IFN- and Th17/Il-23. Il-12 probably acts on naive T cells and the Th1 response is initiated. Il-23 maintains the Th1-mediated inflammatory reaction, stimulates maturation and effects of Th17, and maintains a certain amount of memory cells. We also observe dysfunction of Treg cells, which are responsible for the destruction of autoreactive lymphocytes. In addition, psoriatic keratinocytes have increased resistance to apoptosis, which eliminate damaged cells so that they cannot be recognized as a foreign antigen. However, researchers have suggested that initially the polyclonal activation of T lymphocytes is induced by superantigens (e.g. streptococcal M protein, peptidoglycan) or skin trauma (Koebner phenomenon), whereas in the later phase self-antigens in the epidermis are recognized by autoreactive T cells (keratin K 17, HPV 5 proteins L1, Pso p27), leading to autoimmunity.